Centennials and brands: Perceptions of Central American university students - Berlioz Pastor, José Guillermo; Bermúdez Díaz, Sonia Iveth (LACCEI, 2025)
The study examines an underexplored area of research: the awareness gap between commercial and private brands among university students. Through a quantitative non-probabilistic survey of 154 university centennial students at private universities, the research aimed to understand how branding elements influenced their purchasing decisions. The findings emphasize the urgent need to establish a stronger bond between centennial consumers and products under private labels due to the prevailing lack of awareness and the challenges faced by private brands in attracting university students. Addressing these issues requires a comprehensive approach involving educational initiatives and strategic marketing efforts to establish a deeper connection between private labels and the centennial consumer base.